Development Of Anti-Stress Functional Herbal Drinks Holistic Care Based To Reduce Factors Triggers Of Adolescent Risky Behavior - Shinny Ria Pratiwi; Roslinawati; Lailatun; Puput Sri Mulyani (International Journal of Health and Pharmaceutical (IJHP), 2026)
Adolescence is a developmental phase vulnerable to psychological stress due to academic demands, excessive use of gadgets, irregular sleep patterns, and complex socio-emotional changes. Uncontrolled stress can trigger risky behavior in adolescents, necessitating safe, natural, and sustainable preventive interventions. A holistic care approach through the development of functional herbal anti-stress drinks is a non-pharmacological alternative that has the potential to help reduce stress levels and improve psychological balance in adolescents. This study used a quasi-experimental method with a non-equivalent control group design to analyze the effectiveness of a holistic care-based functional herbal anti-stress drink on reducing the triggers of risky behavior in adolescents. Sixty-four respondents were selected using purposive sampling and divided into an intervention group (n=32) and a control group (n=32). The intervention group was given the functional herbal drink in a structured manner for 12 days, controlling for confounding variables including age, sleep patterns, and device use. Statistical analysis showed a significant reduction in stress levels in the intervention group based on the Wilcoxon test (Z = -4.953; p = 0.000). The mean gain score for stress reduction in the intervention group was 9.40 points, higher than the 1.10 points in the control group. The Mann-Whitney test also showed a significant difference in effectiveness between the two groups (p = 0.000). The conclusion is that the development of a functional herbal anti-stress drink based on holistic care is effective in reducing stress levels and risk-taking behavior triggers in adolescents. These findings are recommended as an alternative promotive and preventive intervention in adolescent health programs in educational settings.